Model Program Khutbah Jumat Di Masjid Al-Ikhlash Surabaya: Perspektif Manajemen Operasi - Isa Saleh; Muhammad Ahnaf Dzikrulloh; Ahmad Habibul Muiz (Masjiduna : Junal Ilmiah Stidki Ar-Rahmah, 2019)
ABSTRACTThis research is intended to describe the program management sermon Friday at the Al-Ikhlash mosque, Tanjung Perak in Surabaya in Ecstasy. The goal in this study was describe the idea in search management program comes in Mosque Al-Ikhlash Tanjung Perak Surabaya in Ecstasy, described the selection process khatib, describes the design introduction, describes the implementation of the trial and described the shape of the design eventually. This study uses qualitative methods with the descriptive approach. This research uses data collection techniques in the form of in-depth interviews, observation and documentation. Program management ' preaching Friday at Mosque Al-Ikhlash of Tanjung Perak Surabaya Aware include: the Groove, the duration of the sermon, the criteria of khatib, theme, schedule khatib, SOP appearance khatib and infrastructure repair facility that supports the sermon Friday. Advice for all administrators that are in Al-Ikhlash mosque in Surabaya, to always provide service properly to the jama'ah, through the care facilities in Mosque Al-Ikhlash, choose a quality khatib-khatib, to performing at home and feel comfortable when the worship in the Mosque of Al-Ikhlash. ABSTRAKPenelitian ini dimaksudkan untuk menggambarkan manajemen program khutbah Jum’at di Masjid Al-Ikhlash  Tanjung Sadari Perak Surabaya. Tujuan dalam penelitian ini adalah menggambarkan pencarian gagasan dalam manajemen program khutbah di Masjid Al-Ikhlash Tanjung Sadari Perak Surabaya, menggambarkan proses seleksi khatib, menggambarkan design pendahuluan, menggambarkan pelaksanaan uji coba dan menggambarkan bentuk design akhirnya. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif. Penelitian ini menggunakan teknik pengumpulan data berupa wawancara mendalam, observasi dan dokumentasi. Manajemen Program khutbah Jum’at di Masjid Al-Ikhlash Tanjung Sadari Perak Surabaya meliputi: alur, durasi khutbah, kriteria khatib, tema, jadwal khatib, SOP penampilan khatib dan sarana prasana yang mendukung khutbah Jum’at. Saran bagi segenap pengurus yang ada di Masjid Al-Ikhlash Surabaya, agar selalu memberikan pelayanan dengan baik kepada para jama’ah, melalui perawatan fasilitas yang ada di Masjid Al-Ikhlash, memilih khatib-khatib yang berkualitas, agar jama’ah betah dan merasa nyaman ketika beribadah di Masjid Al-Ikhlash.